Validitas E–LKPD Matematika Berbasis Tri N Pada Pokok Bahasan Bentuk Aljabar - Nurul Istiqomah; Tri Astuti Arigiyati; Astuti Wijayanti; Sri Adi Widodo (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2021)
The purpose of this study was to design and determine the validity of the Tri N-based Mathematics E-LKPD to improve the critical thinking skills of junior high school students on the subject of algebraic forms. This type of research is research and development which refers to the 4D development procedure which consists of 4 stages, namely define, design, develop, and disseminate. However, this research was only conducted up to the develop stage. The result of this research is that a product has been developed in the form of Tri N-based Mathematics E-LKPD to improve the critical thinking skills of junior high school students on the subject matter of algebraic forms and the validity of the E-LKPD based on the validation results of 9 validators, the calculation of V Aiken with a range of V Aiken is at 0.728 to 1 fall into the high validity category.